Institutions and the school-to-work transition: disentangling the role of the macro-institutional context. (10th September 2016) - Barbieri, Paolo; Cutuli, Giorgio; Passaretta, Giampiero
Abstract: This article explores cross-national variations in young school-leavers' labour market entry process across 17 European countries from 1995 to 2009. The general aim is to disentangle the role of the macro-contexts by analysing the influence of a series of institutional factors on the speed of the school-to-work transition and the prestige of the first relevant job. The influence of the vocational orientation of the educational systems, the employment protection legislation and the product market regulation are theoretically considered and empirically evaluated. Relying on micro-data from the 2009 Ad Hoc Module of the European Labour Survey, we disentangle the role of long-term institutional settings and the influence of short-term institutional changes. Moreover, we test for a possible institutional macro-level trade-off between speed and quality of the school-to-work transition. Finally, we find evidence of significant interactions between the employment protection and vocational orientation of the educational system and between product- and labour market regulation.